Innovative conservation tillage and weed management techniques under rice maize-cowpea system for higher productivity, resource use efficiency and healthy soil in coastal Odisha - Pradhan, S; Garnayak, L M; Dash, R; Behera, R D; Bharteey, P K; Dandasena, S; Priyadarshini, S; Hazarika, N; Hussain, S; Borah, S R; et al. (Plant Science Today, 2025)
In rice-growing regions of India particularly in Odisha, tillage intensive cropping practices have reduced soil organic carbon (SOC) levels and declined soil physical properties. The productivity of crops has therefore decreased over time, indicating a requirement for sustainable substitutes. In this context, a long-term field investigation (2016—2018) was undertaken at the Central Research Station (CRS) of Odisha University of Agriculture and Technology, Bhubaneswar, to assess the effects of conservation tillage and weed management practices on the productivity, resource-use efficiency (RUE) and economics of a rice-based cropping system under sandy loam Typic Endoaquepts. The experiment, laid out in a strip-plot design with three replications, evaluated five crop establishment and residue management practices, viz., conventional tillage (CT), zero tillage (ZT), direct-seeded rice (DSR) and their combinations with residue retention, alongside three weed management strategies, i.e., herbicide-based, manual/mechanical and integrated weed management (IWM). Among the tested combinations, the CT (DSR)-CT-ZT sequence recorded the highest rice equivalent yield (REY) of 13.86 t/ha, system productivity of 37.96 kg REY/ha/day and sustainable yield index (SYI) of 0.79. IWM across all crops enhanced REY (13.84 t/ha) and system productivity (37.42 kg REY/ha/day), outperforming sole herbicide use and hand weeding. The best-performing treatment combination, CT (DSR)-CT-ZT with IWM, achieved the maximum REY (14.58 t/ha), nutrient uptake (327 kg N (nitrogen), 115 kg P (phosphorus), 349 kg K (potassium)/ha), net returns (₹ 122535/ha) and benefit-cost ratio (2.48). The RUE ranking was CT (DSR)-CT-ZT > CT (TPR)-ZT-ZT > (ZT (DSR) + R)-(ZT+R)-ZT > CT (TPR)-CT-F > ZT (DSR)-ZT-ZT. These findings underscore CT (DSR)-CT-ZT with IWM as a promising strategy under conservation agriculture, promoting long-term sustainability and enhanced system productivity through improved resource utilization and soil quality.